2016
DOI: 10.5812/ijem.36091
|View full text |Cite
|
Sign up to set email alerts
|

Care of the Athlete With Type 1 Diabetes Mellitus: A Clinical Review

Abstract: ContextType 1 diabetes mellitus (T1DM) results from a highly specific immune-mediated destruction of pancreatic β cells, resulting in chronic hyperglycemia. For many years, one of the mainstays of therapy for patients with T1DM has been exercise balanced with appropriate medications and medical nutrition. Compared to healthy peers, athletes with T1DM experience nearly all the same health-related benefits from exercise. Despite these benefits, effective management of the T1DM athlete is a constant challenge due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 77 publications
0
27
0
9
Order By: Relevance
“…The study of Danish pediatric cohort indicated high HbA 1c levels and elevated blood pressure as risk factors for progression of DR. 25 Owing to its beneficial influence on metabolic control, a regular physical activity is one of the treatment recommendations in diabetes. 8 However, we must emphasize that patients with proliferative DR are advised to avoid intensive physical activity, which is associated with the risk of vitreous hemorrhage, until the completion of laser therapy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of Danish pediatric cohort indicated high HbA 1c levels and elevated blood pressure as risk factors for progression of DR. 25 Owing to its beneficial influence on metabolic control, a regular physical activity is one of the treatment recommendations in diabetes. 8 However, we must emphasize that patients with proliferative DR are advised to avoid intensive physical activity, which is associated with the risk of vitreous hemorrhage, until the completion of laser therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the activated AMPK elicits glucose transport and desirable lipid metabolism. 8 An inverse association between physical activity and retinopathy or microalbuminuria has been reported among adults with type 1 diabetes. 9 Moreover, a positive effect of regular aerobic exercise on laboratory parameters in type 2 diabetes patients with diabetic peripheral neuropathy was noted already after 8 weeks.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chociaż ogólne zalecenia dotyczące przyjmowania przez sportowców składników odżywczych zostały zawarte w oświadczeniu wydanym po przyjęciu wspólnego stanowiska przez American Dietetic Association i Dietitians of Canada oraz American College of Sports Medicine [36], to każdy przypadek aktywnej fizycznie osoby z T1DM powinien być potraktowany indywidualnie z uwzględnieniem specyfiki realizowanych wysiłków fizycznych przy ścisłej współpracy z lekarzem i dietetykiem oraz innych osób wchodzą-cych w skład zespołu opieki zdrowotnej [37]. Wydaje się też, że wskazywanie korzystnych efektów wynikających z udziału w AF, zachęcanie do niej oraz zapewnianie możliwości bezpiecznego i atrakcyjnego uczestnictwa już od dzieciństwa, może sprzyjać w kontynuacji utrzymywania aktywnego trybu życia w wieku dorosłym, co jest niezmiernie ważne w profilaktyce długoterminowych powikłań [4,38].…”
Section: Discussionunclassified
“…Although general recommendations concerning nutrient intake by athletes are included in a common statement released by the American Dietetic Association, the Dietitians of Canada and the American College of Sports Medicine [36], every case of a physically active individual with T1DM should be treated individually in cooperation with a doctor, dietitian and other people being part of the healthcare team taking into account the specificity of physical effort [37]. Moreover, it seems that indicating benefits of physical activity, encouraging to take up sports and ensuring safe and active participation since childhood may help T1DM patients to continue an active lifestyle in adult life, which is really significant in the prevention of long-term complications [4,38].…”
Section: Wnioskimentioning
confidence: 99%